Development of Treasury's new model of Australian retirement incomes and assets: MARIA - Bruce Bastian; Matthew Smith; Belinda Cheong; Virginia Pineda; Martin Stevenson; Owen Hutchison; Madeleine Nargar; Susie Kluth (The Australian Government, The Treasury, 2017)
Treasury currently has a project underway to significantly enhance its capability to produce detailed modelling of retirement incomes in Australia. The Model of Australian Retirement Incomes and Assets (MARIA) is a long-term dynamic microsimulation model of Australia's retirement income system. When fully operational, MARIA will provide whole-of-population projections beyond the medium term of: Age Pension expenditure and take-up; superannuation funds under management; and retirement income adequacy. It will also enable detailed distributional analysis of both current and hypothetical policy settings. This paper provides high-level details of the model and outlines a number of challenges and research questions for further consideration by Treasury and interested researchers.
Keywords: 330; Retirement incomes; superannuation; pensions; modelling; microsimulation; Tax Analysis Division; Revenue Group